Hospital efficiency in the eastern mediterranean region: A systematic review and meta-analysis - Ravaghi, Hamid; Afshari, Mahnaz; Isfahani, Parvaneh; Mahboub-Ahari, Alireza; Bélorgeot, Victoria D. (Frontiers in Public Health, 2023)
Background: Recent rising costs and shortages of healthcare resources make it necessary to address the issue of hospital efficiency. Increasing the efficiency of hospitals can result in better and sustainable achievement of their organizational goals.The purpose of the present research is to examine hospital efficiency in the East-ern Mediterranean Region (EMR) using DEA. Methods: This study is a systematic review and meta-analysis of all articles published on hospital efficiency in Eastern Mediterranean countries between January 1999 and September 2020, identified by searching three databases (PubMed through MEDLINE, Web of Science, Scopus and Science Direct) and one search engine (Google Scholar). The reference lists of these articles were checked for additional relevant studies. 37 articles were finally selected, and data was analyzed through the Comprehensive Meta-Analysis Software (v.2.2.064). Results: Using the random-effects model, the mean hospital efficiency in Eastern Mediterranean hospitals was 0.882 ± 0.01 at 95% CI. Technical efficiency (TE) was higher in some countries such as such as Iraq (0.976±0.035), Oman (0.926 ± 0.032), and Iran (0.921 ±0.012). A significant statistical correlation was ob-served between the hospital efficiency and the year of publication and sample size (p < .05). Conclusion: Efficiency plays a significant role in hospital growth and development. It is therefore important for healthcare managers and policymakers in the EMR to identify the causes of inefficiency, to improve TE and develop cost-effective strategies.